Peran Public Relations dalam Manajemen Isu dan Komunikasi Krisis - Yeni Usman (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Public relation is a broad field that involves relationships with various stakeholders, especially the relationship between organization and its publics. The roles of public relation in technology information era are significant to establish reciprocal relationship and planned communication between organization and its public. Public relation is a function of strategic management that communicates to engender understanding dan acceptance of its external and internal public. Public relation activities will be determining the repositioning of organization, restoring image and reputation to build new credibility. Public relations capability in issues and public opinion management are required by organization to overcome the crisis that might occur in the organization. Public relation plays role in explanation or defense on unfavorable view of the organization from its public by providing data, facts and information.